CÓ : a/b=b/c=c/d Tính b,c
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đề đúng
\(\frac{a}{b+c+d}+1=\frac{b}{a+c+d}+1=\frac{c}{a+b+d}+1=\frac{d}{a+c+b}+1\)
\(\Leftrightarrow\frac{a+b+c+d}{b+c+d}=\frac{a+b+c+d}{a+c+d}=\frac{a+b+c+d}{a+b+d}=\frac{a+b+c+d}{a+c+b}\)
=> b+c+d = a+c+d = a+b+d = a+c+b
=> a=b=c=d
=> GTBT = 1+1+1+1 =4
a/b=b/c=c/a=a+b+c/b+c+a=1
⇒a/b=b/c=c/a=1
=> a = b = c = 2013
Vậy b = 2013; c = 2013
\(\frac{a}{b+c+d}=\frac{b}{c+d+a}=\frac{c}{a+b+d}=\frac{d}{a+b+c}=\frac{a+b+c+d}{3\left(a+b+c+d\right)}=\frac{1}{3}.\)
\(\Rightarrow\hept{\begin{cases}3a=b+c+d\\3b=a+c+d\end{cases};\hept{\begin{cases}3c=a+b+d\\3d=a+b+c\end{cases}}}\)
Trừ vế theo vế ta có :\(\hept{\begin{cases}3\left(a-b\right)=b-a\\3\left(b-c\right)=c-b\\3\left(c-d\right)=d-c\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}a-b=b-a=0\\b-c=c-b=0\\c-d=d-c=0\end{cases}}\)\(\Leftrightarrow\hept{\begin{cases}a=b\\b=c\\c=d\end{cases}}\)=>a=b=c=d
\(\Rightarrow M=1+1+1+1=4\)
Giải : Ta có: \(\frac{a}{b+c+d}=\frac{b}{c+d+a}=\frac{c}{d+a+b}=\frac{d}{b+c+a}\)
=> \(\frac{b+c+d}{a}=\frac{c+d+a}{b}=\frac{d+a+b}{c}=\frac{b+c+a}{d}\)
=> \(\frac{b+c+d}{a}+1=\frac{c+d+a}{b}+1=\frac{d+a+b}{c}+1=\frac{b+c+a}{d}+1\)
=> \(\frac{a+b+c+d}{a}=\frac{a+b+c+d}{b}=\frac{a+b+c+d}{c}=\frac{a+b+c+d}{d}\)
=> \(\frac{1}{a}=\frac{1}{b}=\frac{1}{c}=\frac{1}{d}\) => a = b = c = d
Khi đó, ta có: M = \(\frac{a+b}{c+d}+\frac{b+c}{a+d}+\frac{c+d}{a+b}+\frac{d+a}{b+c}\)
= \(\frac{a+a}{a+a}+\frac{b+b}{b+b}+\frac{c+c}{c+c}+\frac{d+d}{d+d}\)
= \(1+1+1+1=4\)